PEMODELAN ALIRAN MATERIAL SEDIMEN AKIBAT ARUS PASANG SURUT UNTUK PEMELIHARAAN KEDALAMAN PERAIRAN PELABUHAN (Studi Kasus :Pelabuhan Tanjung Perak-Teluk Lamong, Surabaya) - Kurniawan, Akbar; Pradana, Ramanda Aji (Geoid, 2016)
Tides is a phenomenon rise and fall of the sea water periodically due to moon and sun gravity. Tides able to raise ocean current is called a tidal current. A tidal current influence the transport of sediment contained in the waters. The process of the deposition of sediment in the waters can affected the shape of topography at the base of waters, one of them is called silting up. The silting up of the sea waters can cause problems if there is in port waters, especially in the ways of shipping and port ponds. The depth of the sea no longer in accordance with the draft of the boats can cause a ship crash. Hence, it needs maintenance the depth of port waters territory by port authority.In this research, done modelling the flow of sediment material due to a tidal current to know the location where happened the largest depth changing in order maintenance the depth in port waters. Modelling the stream and the flow of sediment done in a numerical simulation on tides and grain size parameter. Based on the result of modelling, the largest sediment material flow happened in the estuary of Kali Semampir at coordinate (693905,38; 9204010,30) when the tides is high, with solid flux value 0,000584 m³/s. While the greatest of depth waters change in port ponds Zamrud with the change equals 0,9 m, so that it needs waters depth monitoring in this area routinely